The effectiveness of therapy with valsartan and hydrochlorothiazide and its effect on the left atrial myocardium condition in women with arterial hypertension in postmenopause - M. Yu. Kolesnyk; M. V. Sokolova (Zaporozhye State Medical University, 2019)
Purpose - to evaluate the effectiveness of the combination of valsartan and hydrochlorothiazide and its effect on the structural and functional parameters of the left atrial myocardium in postmenopausal women with arterial hypertension. Materials and methods. An open prospective controlled study included 100 postmenopausal women with uncomplicated arterial hypertension. Transthoracic and speckle tracking echocardiography was performed on a Vivid E9 XDClear Console 4D Expert 100 ultrasound scanner (General Electric, USA) with ECG-synchronization. Ambulatory blood pressure monitoring was performed using the device ABPM-04 (Meditech, Hungary). After 6 months of treatment with the antihypertensive combination of valsartan and hydrochlorothiazide, all women were re-examined in full. Statistical analysis of the results was performed using the Statistica 13.0 software package. All tests were two-way, statistically significant considered differences at P < 0.05. Results. As a result of our study, office systolic and office diastolic blood pressure in postmenopausal women with arterial hypertension significantly decreased (P < 0.001) due to a 6-month treatment with valsartan and hydrochlorothiazide. The target level of blood pressure, according to office measurements, was reached by 64 % of patients. A significant decrease of the SBP time index in the daytime in 1.6 times (P = 0.012), morning rise of SBP (P = 0.021) and the average pulse blood pressure (P = 0.012) was observed. Analysis of the LA deformation dynamics under the 6-month antihypertensive therapy did not reveal significant changes in the longitudinal strain of the LA in postmenopausal women with AH, unlike left ventricular strain. Conclusions. Combined antihypertensive therapy with valsartan and hydrochlorothiazide in postmenopausal women is effective, safe and well-tolerated. The use of this therapy for 6 months does not significantly affect the size and deformation properties of the left atrium, in contrast to the positive structural and functional remodeling of the left ventricle.